Glycine is a transmitter in the human and chimpanzee cochlear nuclei - Baizer, Joan S.; Sherwood, Chet C.; Hof, Patrick R.; Baker, James F.; Witelson, Sandra F. (Frontiers in Neuroanatomy, 2024)
Introduction Auditory information is relayed from the cochlea via the eighth cranial nerve to the dorsal and ventral cochlear nuclei (DCN, VCN). The organization, neurochemistry and circuitry of the cochlear nuclei (CN) have been studied in many species. It is well-established that glycine is an inhibitory transmitter in the CN of rodents and cats, with glycinergic cells in the DCN and VCN. There are, however, major differences in the laminar and cellular organization of the DCN between humans (and other primates) and rodents and cats. We therefore asked whether there might also be differences in glycinergic neurotransmission in the CN. Methods We studied brainstem sections from humans, chimpanzees, and cats. We used antibodies to glycine receptors (GLYR) to identify neurons receiving glycinergic input, and antibodies to the neuronal glycine transporter (GLYT2) to immunolabel glycinergic axons and terminals. We also examined archival sections immunostained for calretinin (CR) and nonphosphorylated neurofilament protein (NPNFP) to try to locate the octopus cell area (OCA), a region in the VCN that rodents has minimal glycinergic input. Results In humans and chimpanzees we found widespread immunolabel for glycine receptors in DCN and in the posterior (PVCN) and anterior (AVCN) divisions of the VCN. We found a parallel distribution of GLYT2-immunolabeled fibers and puncta. The data also suggest that, as in rodents, a region containing octopus cells in cats, humans and chimpanzees has little glycinergic input. Discussion Our results show that glycine is a major transmitter in the human and chimpanzee CN, despite the species differences in DCN organization. The sources of the glycinergic input to the CN in humans and chimpanzees are not known.